A Digitally Controllable Polymer-Based Microfluidic Mixing Module Array - Raymond H. W. Lam; Wen J. Li (Micromachines, 2012)
This paper presents an integrated digitally controllable microfluidic system for continuous solution supply with a real-time concentration control. This system contains multiple independently operating mixing modules, each integrated with two vortex micropumps, two Tesla valves and a micromixer. The interior surface of the system is made of biocompatible materials using a polymer micro-fabrication process and thus its operation can be applied to chemicals and bio-reagents. In each module, pumping of fluid is achieved by the vortex micropump working with the rotation of a micro-impeller. The downstream fluid mixing is based on mechanical vibrations driven by a lead zirconate titanate ceramic diaphragm actuator located below the mixing chamber. We have conducted experiments to prove that the addition of the micro-pillar structures to the mixing chamber further improves the mixing performance. We also developed a computer-controlled automated driver system to control the real-time fluid mixing and concentration regulation with the mixing module array. This research demonstrates the integration of digitally controllable polymer-based microfluidic modules as a fully functional system, which has great potential in the automation of many bio-fluid handling processes in bio-related applications.